Single-stapling technique versus hand-sewn anastomosis in inter-sphincteric resection with transanal total mesorectal excision (Super SST): protocol for a multicentre randomized clinical trial. Issue 1 (13th January 2023) - Kitaguchi, Daichi; Wakabayashi, Masashi; Hasegawa, Hiro; Ando, Koji; Ikeda, Koji; Tsukada, Yuichiro; Nishizawa, Yuji; Ito, Masaaki
Abstract: Background: Currently, hand-sewn anastomosis is the standard procedure for inter-sphincteric resection (ISR); however, distal purse-string suturing during transanal total mesorectal excision (TaTME) has allowed a single-stapling technique (SST). Although it was originally intended for cases requiring anastomosis of 2 cm or more above the anorectal junction (ARJ), SST could be safely performed in ISR. The aim of this trial is to determine the superiority of SST over hand-sewn anastomosis in ISR with TaTME. Methods: The Super SST trial is a multicentre randomized clinical trial comparing stapled and hand-sewn anastomoses in ISR with TaTME. The trial will recruit patients scheduled for TaTME with anastomosis below the ARJ, who will be allocated 1:1 to receive either hand-sewn or stapled anastomosis. The primary endpoint is anastomosis-related complications within 30 postoperative days. Secondary endpoints include all early and late complications, operating time, reoperation, mortality rate, length of postoperative hospital stay, readmission, incidence of anal pain and rectal mucosal prolapse, length of temporary stoma retention, the proportion of patients with a temporary stoma at 1 year after surgery, and anorectal function at 1 year after surgery. Conclusion: This trial will provide important clinical insights for new and promising anastomotic options for patients with very low rectal cancer. Registration number: UMIN000047818 (https://www.umin.ac.jp/ctr/index-j.htme ). Abstract : The Super SST trial is a multicentre randomized clinical trial comparing stapled and hand-sewn anastomosis in inter-sphincteric resection (ISR) with transanal total mesorectal excision (TaTME). Because the single-stapling technique (SST) was originally proposed for cases that require anastomosis superior to the anorectal junction, this study aims to determine the superiority of SST over hand-sewn anastomosis in ISR with TaTME, which has not been evaluated. This trial will provide important clinical insights for new and promising anastomotic options for patients with very low rectal cancer.